Pursed Lips Breathing Therapy for Ineffective Respiratory Patterns in Pneumonia Patients - Sri Andayani; Badriyah , Umi Nurul (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2024)
Pneumonia, a persistent major health concern in developing countries, often leads to ineffective breathing patterns in those affected. This case study aimed to evaluate the effectiveness of Pursed Lips Breathing (PLB) therapy in improving oxygenation status and addressing ineffective breathing patterns in a pneumonia patient at 'Aisyiyah Ponorogo General Hospital. Using a descriptive approach and nursing process framework, the intervention involved PLB exercises for 10 minutes, twice daily, for 5 days, combined with oxygen administration, semi-Fowler positioning, and bronchodilator therapy. Prior to the intervention, the patient presented with shortness of breath, ineffective cough, a respiratory rate of 27 breaths per minute, and oxygen saturation of 93%. Following the 5-day intervention, the patient reported no further shortness of breath, reduced coughing, and improved oxygen saturation. This study concludes that PLB therapy is effective in improving oxygenation status and addressing ineffective breathing patterns in pneumonia patients, although further research with a larger sample size is recommended to corroborate these findings.